2012
DOI: 10.1371/journal.pone.0037767
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-Like Receptors in the Developing Brain

Abstract: Toll-like receptors (TLR) are key players of the innate and adaptive immune response in vertebrates. The original protein Toll in Drosophila melanogaster regulates both host defense and morphogenesis during development. Making use of real-time PCR, in situ hybridization, and immunohistochemistry we systematically examined the expression of TLR1–9 and the intracellular adaptor molecules MyD88 and TRIF during development of the mouse brain. Expression of TLR7 and TLR9 in the brain was strongly regulated during d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 31 publications
4
96
0
1
Order By: Relevance
“…It is also extensively expressed in the central nervous system [12,28], and its activation has been shown to correlate with many neuropsychiatric conditions including depression and drug addiction [12,29]. TLR4 activation triggers a cascade of signaling events leading to the release of many proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…It is also extensively expressed in the central nervous system [12,28], and its activation has been shown to correlate with many neuropsychiatric conditions including depression and drug addiction [12,29]. TLR4 activation triggers a cascade of signaling events leading to the release of many proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they concluded that the negative effect of R848 is mediated via TLR8 but not TLR7 [31] . However, their results are in conflict to many recent studies from various laboratories regarding the expression of TLR7 in neurons [10,11,20,32] , as evidenced by the results of in situ hybridization, quantitative polymerase chain reaction (Q-PCR), and immunostaining using TLR7 antibodies [10,11,20,32] . Actually, the expression level of TLR7 in neurons is even higher than that of TLR8 [11] .…”
Section: Tlrs and Neuronal Morphogenesismentioning
confidence: 70%
“…Furthermore, Kaul and colleagues performed quantitative PCR to examine the expression levels of TLR1, TLR2, TLR3, TLR4, TLR5, TLR6, TLR7, TLR8, and TLR9 in developing brains and found that the levels of TLR7 and TLR9 correlated particularly well with brain development [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR3 mRNA has also been detected in epithelial cells of many different organs including airway, uterine, corneal, vaginal, biliary, and intestinal organs because the mucous membranes of these organs act as efficient innate barriers to infection from the respiratory tract, and gastrointestinal and urogenital systems [6,16]. Surprisingly, higher expression level of TLR3 is also observed in neurons, astrocytes, and microglia, suggesting a specific function in response to encephalitogenic viruses of the central nervous system [6,17,18]. TLRs 7 and 9 are predominantly expressed in plasmacytoid DCs ( pDCs) in humans and are involved in strong IFN-a induction, but TLR8 tends to be detected in human monocytes and mDCs, and predisposes the induction of inflammatory cytokines [1,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%